Originally Posted by

**reefcake** Hi I'm studying forensics and i need help understanding how to work these out.I know how to rearrange formulae I'm just having trouble applying it to these type of equations. Help would be very much appreciated

The question states that I must combine the formulae so that I remove the letter in bold from the resulting equation.

6-2**q**=r and T=3**q**rs

here is what i've done so far

T=3qrs . i divide the r

t/r=3qs then I multiply the t

r=3qst this allows me to combine it with the first equation

6-2**q**=3**q**st

the problem that i now have is how to arrange this formulae as the question stated.

to remove the **q** this is where I'm at a loss and my attempts have failed

if I be could showed the method it would be great.

thanks

reefcake

Welcome to MHF.

Solve one of the equations for **q**. The following one may be easiest.INDENT]T=3**q**rs[/INDENT]

Then take whatever it is that you find **q** is equal to, and substitute that for **q** in the other equation 6-2(**whatever q is equal to**)=r